Sistem Informasi Ketersediaan Ruangan Rumah Sakit Terintegrasi Aplicare BPJS Kesehatan - Albert Riyandi (Paradigma, 2019)
health is a very basic thing in the needs of every human being this is also regulated in the 1945 Constitution. The government in realizing health services mandated by the law has a national health insurance program (JKN) organized by the Health Social Security Organizing Agency (BPJS Health). This JKN program until December 31, 2017 the number of participants who participated had reached 187,982,949 which means 72.9% of the Indonesian population. Aplicares is an application of a health BPJS that functions to find locations and information about the desired health facilities that can be seen on the web of health facilities.bpjs-kesehatan.go.id/aplicares. Hospitals that have collaborated with health BPJS are required to be able to enter the room data they have into the aplicares and be updated continuously even in real time. Poor hospitals IT experts who understand programming languages have difficulty entering data because BPJS Health only provides scripting and examples of programming languages. Existing Hospital Information Systems (SIM-RS) are usually made by Developer Systems outside of Hospital staff, so to add new modules must add additional costs. With the Information System Availability of Integrated Hospital Rooms with BPJS Health Aplicares that are built with Motede Waterfall, it becomes the solution to these problems